Enhancing Self-Esteem, Self-Efficacy, and Academic Buoyancy through Positive Thinking Training in College Students - Ziba Nouri; Firozeh Khalil Abadinejad (Iranian Evolutionary Educational Psychology Journal)
Objective: This study was undertaken with the objective of examining the efficacy of positive thinking training on the self-esteem, self-efficacy, and academic buoyancy of students. Methods: This study employed a quasi-experimental design featuring a pre-test and post-test framework, encompassing both experimental and control groups. Among the student population enrolled at Payam Noor University, Kish branch in 2023, a sample of 30 students was selected using the accessible sampling method, divided at random into two distinct groups. For data collection, in addition to a demographic information checklist created by the researcher, the Rosenberg self-esteem questionnaire, the Sherer's General Self-Efficacy Scale, and the Academic buoyancy questionnaire developed by Hosseinchari and Dehghanizadeh were employed. The intervention program was executed in accordance with the positive thinking training package devised by Seligman et al., spanning 10 sessions, each lasting 1.5 hours on a weekly basis. Data analysis was conducted by testing the assumptions underlying parametric statistics and performing analysis of covariance utilizing SPSS-26. Results: The results demonstrated that there existed a statistically significant change in self-esteem (F=11.15, P=0.007, and η=0.588), academic buoyancy (F=16.84, P=0.018, and η=0.603), as well as self-efficacy belief and its associated dimensions (F=13.10, P=0.015, and η=0.612) when comparing the experimental group with the control group. Conclusions: Consequently, the results of this research substantiate the influence of positive thinking training on the motivational frameworks of students and propose it as a viable strategy to enhance the motivational and psychological well-being of students.